Behind the Intifada : labor and women's movements in the occupied territories - Hiltermann, Joost R. (Princeton studies on the Near East., 1991)
Before the intifada began, Joost Hiltermann had already looked at local organizations in the Israeli-occupied West Bank and Gaza Strip and seen there the main elements that would eventually be used to mobilize the Palestinian masses. In the first comprehensive study of these organizations, Hiltermann shows how local organizers provided basic services unavailable under military rule, while recruiting for the cause of Palestinian nationalism.